A (in)suficiência do aprendizado do direito: um estudo sobre as crises do ensino jurídico brasileiro - Gomes, Yara Alves (2022)
The plurivocity of the concept of Law imposes barriers to the understanding of legal science, which must be conceived in several facets, otherwise its teaching will be insufficient. The legal teaching/learning process must pay attention to the exposition of the classic Law schools that have developed throughout history and contents of a zetetic and dogmatic nature that critically emancipate the bachelor. Through the development of legislative, bibliographical and documental analyses, explanatory research was developed that aims to expose the classic conceptions of the concept of Law, evaluate the crisis factors of legal education in Brazil together, in order to seek to the theme . The infamous crisis in legal education guides studies dating back to the 1950s and is presented in four pillars: the bachelor's degree responsible for providing the bachelor with the acquisition of social status through the occupation of bureaucratic positions; the dystopia between teaching and social reality portrayed through the incompatibility of the Law taught with the time and space in which it is taught; the technization of legal education that synthesizes the course to a limiting normative reproduction and the reduction of legal science to a consumer good that demonstrates the affectation of market impressions, the unrestrained expansion of Law courses in the country and concerns for development of legal education that contemplates social justice and the effectiveness of human dignity. These factors causing crisis together, contemplate the novelty of this work, which observes the need for a gradual opening of the Law course to the study of other social sciences. Transdisciplinarity is the teaching modality that allows the crossing between disciplines and the development of complex learning necessary for the planetary understanding of social problems